Environmentally friendly stabilizer for low-calcium PVC products and preparation method thereof
By preparing a low-calcium PVC environmentally friendly stabilizer made of the main stabilizer, pentaerythritol, uracil, monoglyceride stearate and PE wax, the problems of insufficient environmental pollution, toxicity and stability of existing PVC thermal stabilizers are solved, and the efficient thermal stability and light stability of PVC products are achieved.
Patent Information
- Application Number
- CN202411863971.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing PVC thermal stabilizers have problems of insufficient environmental pollution, toxicity and stability, especially the accumulated toxicity and environmental pollution of lead salt stabilizers, and the traditional stabilizers are insufficient in long-term use.
Through the Fuker reaction and other chemical reactions, an environmentally friendly stabilizer for low-calcium PVC products was prepared. The stabilizer is made of a mixture of main stabilizer, pentaerythritol, uracil, monoglyceride stearate and PE wax in a specific proportion. The main stabilizer has long-term ultraviolet absorption performance and multifunctional thermal stability performance.
This environmentally friendly stabilizer can effectively improve the thermal stability and light stability of PVC products, extend the color change time of PVC products, ensure that it maintains good performance during long-term use, and is environmentally friendly and non-toxic because it does not contain harmful substances such as lead.
Smart Images

Figure CN119320524B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to an environmentally friendly stabilizer for low-calcium PVC products and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the five most common resins in the world. It has good water resistance, weather resistance, insulation and geometric stability, and has strong resistance to oxidants, reducing agents and strong acids. PVC has a wide range of applications and is mainly used in packaging materials, pipes and accessories, transportation, electronics and daily necessities. However, due to the structural defects of PVC, its thermal stability is poor, and a certain amount of heat stabilizer needs to be added to improve its thermal stability.
[0003] PVC heat stabilizers mainly include lead salt stabilizers, organotin stabilizers and metal soap stabilizers. Lead salt stabilizers have excellent long-term heat stability and low manufacturing cost, but they cannot be used to prepare transparent PVC products. They have cumulative toxicity and serious environmental pollution. Organotin stabilizers have good light stability, long-term effect at low temperature and transparency, but the intermediate products in the preparation process of organotin have great environmental pollution and are expensive. Metal soap heat stabilizers are non-toxic and environmentally friendly, but there is a certain gap in stability compared with lead salts and organotin. China is a major producer and consumer of PVC heat stabilizers, accounting for more than 39% of the total global supply of PVC stabilizers. Among them, the amount of PVC products produced using lead salt heat stabilizers accounts for about 35%.
[0004] With the sustainable development of my country's economy and science and technology, people's environmental awareness and health awareness are gradually increasing, and the research of green and efficient PVC heat stabilizers has become a hot topic in the current industry. Therefore, the development of lead-free and environmentally friendly heat stabilizers is an urgent problem to be solved at this stage.
[0005] On the other hand, for transparent soft PVC products with low calcium filling content, such as catheters, PVC cushions or outdoor PVC boards, there are also certain requirements for the light stability of PVC products. Summary of the invention
[0006] The object of the present invention is to provide an environmentally friendly stabilizer for low-calcium PVC products and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0007] In order to achieve the above technical objectives, the technical solution of the present invention is:
[0008] A method for preparing an environmentally friendly stabilizer for low-calcium PVC products comprises mixing a main stabilizer, pentaerythritol, uracil, monoglycerol stearate, and PE wax in a mass ratio of 10:3:2:1:1;
[0009] The preparation method of the main stabilizer comprises the following steps:
[0010] S1, using anhydrous aluminum chloride as a catalyst, 3-hydroxybenzoic acid and cyanuric chloride as raw materials to carry out Friedel-Crafts reaction, after the reaction is completed, cooling, crystallizing and filtering to obtain a solid, and recrystallizing the solid to obtain intermediate I;
[0011] The specific reaction route is as follows:
[0012] ;
[0013] S2, using anhydrous aluminum chloride as a catalyst, intermediate I and resorcinol as raw materials to carry out Friedel-Crafts reaction, after the reaction is completed, pouring the reaction product into a mixed solution containing ice, water and hydrochloric acid to hydrolyze the catalyst, and then standing, heating distillation, vacuum filtering, and drying to obtain intermediate II;
[0014] The specific reaction route is as follows:
[0015] ;
[0016] S3, reacting intermediate II with calcium perchlorate at 60°C for 1 hour, then stopping heating and continuing the reaction for 24 hours, filtering, washing and drying to obtain intermediate III;
[0017] The specific reaction route is as follows:
[0018] ;
[0019] S4, using N,N-dimethylformamide as solvent, the intermediate III reacts with NaOH to obtain the main stabilizer;
[0020] The specific reaction route is as follows:
[0021] .
[0022] As a further improvement, in step S1, the molar ratio of the 3-hydroxybenzoic acid to cyanuric chloride is 1:1.1, the molar ratio of the catalyst anhydrous aluminum chloride to the 3-hydroxybenzoic acid is 1:1, the reaction temperature is 30°C, and the reaction time is 10 hours.
[0023] As a further improvement, in step S2, the molar ratio of the intermediate I to the resorcinol is 1:2, the reaction temperature is 100°C, and the reaction time is 5 hours.
[0024] As a further improvement, in step S3, the molar ratio of the intermediate II to the calcium perchlorate is 1:2.
[0025] As a further improvement, in step S4, the molar ratio of the intermediate III to the NaOH is 1:2.15, the reaction temperature is 50-60° C., and the reaction time is 1 h.
[0026] As a further improvement, in step S1, an aqueous N,N-dimethylformamide solution is used to recrystallize the solid.
[0027] As a further improvement, in step S3, after the reaction is completed, the filtered solid is washed twice with methanol and chloroform respectively, the washed product is dried in a 65°C forced air oven for 3 h, and then placed in a 65°C vacuum oven and dried for 6 h to obtain intermediate III.
[0028] The invention also provides an environmentally friendly stabilizer prepared by a method for preparing an environmentally friendly stabilizer for low-calcium PVC products.
[0029] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] The invention provides a method for preparing an environmentally friendly stabilizer for low-calcium PVC products. The method uses cyanuric chloride as a raw material and prepares an environmentally friendly stabilizer containing triazines and having long-lasting ultraviolet absorption performance through a series of reactions, thereby providing an anti-light aging multifunctional heat stabilizer.
[0031] The PVC heat stabilizer obtained by the present invention has a main stabilizer which can replace unstable chlorine atoms in PVC, causing the degradation of PVC to lose active points, thereby blocking the "zipper-like" degradation of PVC from the source and ensuring that the PVC products have excellent initial whiteness and whiteness retention.
[0032] At the same time, the nitrogen-containing organic anions in the main stabilizer can absorb HCl, especially the lone pair of electrons in the nitrogen atom can absorb HCl. The sodium ions contained in the main stabilizer can further absorb HCl, further enhancing the thermal stability and ensuring that PVC has excellent long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the infrared spectrum of intermediate Ⅰ in Example 1;
[0034] Figure 2 is the infrared spectrum of intermediate II in Example 1;
[0035] Figure 3 is the infrared spectrum of intermediate III in Example 1;
[0036] Figure 4 is the infrared spectrum of the main stabilizer in Example 1;
[0037] Figure 5 This is a graph showing the color change results of the sample in Example 3;
[0038] Figure 6 is a graph showing the ultraviolet absorption performance test results of the environmentally friendly stabilizer in Example 4;
[0039] Figure 7 This is a graph showing the stability test results of the environmentally friendly stabilizer in Example 4 on the ultraviolet absorption performance. DETAILED DESCRIPTION
[0040] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Example 1 A method for preparing an environmentally friendly stabilizer for low-calcium PVC products comprises the following steps:
[0042] S1, preparation of intermediate I;
[0043] 1400L of 1,2-dichloroethane was added to a 2000L reactor, stirred and heated to 30°C. 118.4kg of 98% by mass 3-hydroxybenzoic acid and 113kg of 99.2% by mass anhydrous aluminum chloride were added to the reactor, stirred for 30min, 171.3kg of 99.5% by mass cyanuric chloride was added, and stirred at 30°C for 10h. After the reaction was completed, the reaction mixture was slowly added to 3000L of ice water, solids were precipitated, filtered, and the solids were recrystallized from N,N-dimethylformamide aqueous solution to obtain 224.92kg of intermediate I with a purity of 98.2% and a yield of 91.9%.
[0044] S2, preparation of intermediate II;
[0045] 1200L of chlorobenzene was added to a 2000L reactor, 150kg of 98.2% intermediate I and 119.7kg of 99.5% resorcinol were added to the reactor, and then 138.1kg of 99.5% anhydrous aluminum chloride was added, heated and stirred, and the temperature was raised to 100°C for reaction for 5h; after the reaction, the product was poured into a mixture of ice, water and hydrochloric acid to hydrolyze the catalyst, and then allowed to stand for 12h, heated and distilled, vacuum filtered and dried to obtain 215.12kg of intermediate II with a purity of 98.8% and a yield of 95.2%;
[0046] S3, preparing intermediate III;
[0047] 1500L methanol was added to a 2000L reactor, and 49kg of 98.8% intermediate II and 13.8kg of 98% calcium perchlorate were added to the reactor, stirred and heated to 60°C, reacted for 1h, then stopped heating, stirred and reacted for 24h, filtered to obtain a solid, washed twice with methanol and chloroform, dried in a 65°C forced air oven for 3h, and then dried in a 65°C vacuum oven for 6h, to obtain 45.48kg of intermediate III, with a purity of 97.9% and a yield of 87.9%;
[0048] S4, preparing a primary stabilizer;
[0049] 300L N,N-dimethylformamide was added to a 500L reactor, 4.27kg of 99% NaOH was added to the reactor, heated and stirred, and the temperature was raised to dissolve, and then 45.48kg of 97.9% intermediate III was added, and the temperature was raised to 60°C, and the temperature was maintained, and the reaction was continued for 1h, and then cooled and vacuum filtered to obtain 46.52kg of the main stabilizer with a purity of 99.2% and a yield of 98.9%;
[0050] S5. Mix the main stabilizer, pentaerythritol, uracil, monoglycerol stearate, and PE wax in a mass ratio of 10:3:2:1:1 to obtain an environmentally friendly stabilizer for low-calcium PVC products.
[0051] The structures of the synthesized intermediates Ⅰ, Ⅱ, Ⅲ and the main stabilizer were characterized by Fourier transform infrared spectroscopy. Figure 1-Figure 4 shown.
[0052] Figure 1 is the infrared spectrum of intermediate Ⅰ, Figure 1 It can be seen that at 1700cm -1 There are strong absorption peaks and 2700-3000cm -1 The stretching vibration absorption peak appears near 1600cm -1 、1580cm -1 、1500cm -1 、1450cm -1 There is an absorption peak near the benzene ring, which is the stretching vibration absorption peak at 700-900cm -1 The absorption peak of chlorine atoms appears at 3300cm -1 The absorption peak of hydroxyl group appears nearby.
[0053] Figure 2 is the infrared spectrum of intermediate II, Figure 2It can be seen that the absorption peak of chlorine atoms disappears, indicating that there are no chlorine atoms in intermediate II and the chlorine atoms in cyanuric chloride are completely replaced.
[0054] Figure 3 is the infrared spectrum of intermediate III, Figure 3 It can be seen that the characteristic peak of carboxyl is at 1700 cm -1 It does not appear around 1600cm -1 Around 1400cm -1 Two new characteristic peaks appeared on the left and right. This is because after the carboxyl group combines with calcium ions, the hydrogen on the carboxyl group is replaced by calcium ions, and the C=O and CO on the carboxyl group undergo electron cloud homogenization, which makes the 1700cm -1 The carbonyl characteristic peak at 1600cm -1 Around 1400cm -1 Two new characteristic peaks appeared on the left and right.
[0055] Figure 4 The infrared spectrum of the main stabilizer is Figure 4 It can be seen that 1260cm -1 The characteristic peaks of aromatic ether appeared on the left and right.
[0056] Example 2 A method for preparing an environmentally friendly stabilizer for low-calcium PVC products comprises the following steps:
[0057] S1, preparation of intermediate I;
[0058] 1400L of 1,2-dichloroethane was added to a 2000L reactor, stirred and heated to 30°C, 118.4kg of 98% by mass 3-hydroxybenzoic acid and 113kg of 99.2% by mass anhydrous aluminum chloride were added to the reactor, stirred for 30 minutes, 155.7kg of 99.5% by mass cyanuric chloride was added, and stirred at 30°C for 10 hours. After the reaction was completed, the reaction mixture was slowly added to 3000L of ice water, solids were precipitated, filtered, and the obtained solids were recrystallized from N,N-dimethylformamide aqueous solution to obtain 215.35kg of intermediate I with a purity of 98.7% and a yield of 88.4%.
[0059] S2, preparation of intermediate II;
[0060] 1200L of chlorobenzene was added to a 2000L reactor, 149.3kg of 98.7% intermediate I and 114kg of 99.5% resorcinol were added to the reactor, and 138.1kg of 99.5% anhydrous aluminum chloride was added, heated and stirred, and the temperature was raised to 100°C for reaction for 5h. After the reaction, the product was poured into a mixture of ice, water and hydrochloric acid for hydrolysis, allowed to stand for 10h, heated for distillation, vacuum filtered and dried to obtain 208.25kg of intermediate II with a purity of 98.2% and a yield of 91.6%.
[0061] S3, preparing intermediate III;
[0062] 1500L methanol was added to a 2000L reactor, and 49.3kg of intermediate II with a mass fraction of 92.2% and 13.8kg of calcium perchlorate with a mass fraction of 98% were added to the reactor, and the mixture was heated to 60°C with stirring, and the reaction was continued for 1h. Then the heating was stopped, and the reaction was continued with stirring for 24h. The solid was filtered to obtain a solid, and the solid was washed twice with methanol and chloroform. The washed product was dried in a 65°C forced air oven for 3h, and then dried in a 65°C vacuum oven for 6h to obtain 45.86kg of intermediate III with a purity of 97.1% and a yield of 87.9%.
[0063] S4, preparing a primary stabilizer;
[0064] 300L N,N-dimethylformamide was added to a 500L reactor, 3.97kg of 99% NaOH was added to the reactor, heated and stirred, and the temperature was raised to dissolve, and then 45.86kg of 97.1% intermediate III was added, and the temperature was raised to 50°C, and the temperature was maintained, and the reaction was continued for 1h, and then cooled and vacuum filtered to obtain 44.4kg of the main stabilizer with a purity of 99% and a yield of 94.2%;
[0065] S5. Mix the main stabilizer, pentaerythritol, uracil, monoglycerol stearate, and PE wax in a mass ratio of 10:3:2:1:1 to obtain an environmentally friendly stabilizer for low-calcium PVC products.
[0066] Example 3 The thermal stability performance test of the environmentally friendly stabilizer prepared by the present invention is as follows:
[0067] The traditional calcium zinc stearate heat stabilizer is mixed with pentaerythritol, uracil, monoglycerol stearate and PE wax in a mass ratio of 10:3:2:1:1 to obtain the calcium zinc stearate PVC heat stabilizer.
[0068] Experimental group: 100 parts of each of 5 groups of PVC (polyvinyl chloride) were taken, namely Group A1, Group A2, Group A3, Group A4, and Group A5. Group A1 added 1 part of the environmentally friendly stabilizer prepared in Example 1, Group A2 added 2 parts of the environmentally friendly stabilizer prepared in Example 2, Group A3 added 3 parts of the environmentally friendly stabilizer prepared in Example 1, Group A4 added 4 parts of the environmentally friendly stabilizer prepared in Example 1, and Group A5 added 5 parts of the environmentally friendly stabilizer prepared in Example 1.
[0069] Control group: 100 portions of each of 4 groups of PVC (polyvinyl chloride) were taken, namely group a1, group a2, group a3 and group a4. 1 portion of calcium zinc stearate PVC heat stabilizer was added to group a1, 2 portions of calcium zinc stearate PVC heat stabilizer was added to group a2, 3 portions of calcium zinc stearate PVC heat stabilizer was added to group a3, and 4 portions of calcium zinc stearate PVC heat stabilizer was added to group a4.
[0070] The mixed 9 groups of materials were respectively refined on a double-roll mill at 180℃ for 120s, and the samples obtained by the refinement were pressed into samples of length 3cm×width 3cm×thickness 0.2cm in a fully automatic tablet press. The 9 samples were placed on aluminum foil respectively, and the aluminum foil and the samples were placed on a bracket and placed in a 180℃ blast oven. The samples were taken out every 10 minutes, and the color changes of the samples were observed and recorded until the color of the samples turned black. The quality of the thermal stability of the heat stabilizer in PVC was judged according to the degree of color change of the samples. The experimental results are shown in the figure. Figure 5 shown.
[0071] Depend on Figure 5 It can be seen that the environmentally friendly stabilizer prepared by the present invention can significantly prolong the discoloration time of PVC compared with the traditional calcium zinc stearate heat stabilizer, and has good medium- and long-term thermal stability. When the addition amount of the environmentally friendly stabilizer prepared by the present invention is 4 parts, the thermal stability is the best, and when the addition amount is 5 parts, the thermal stability is similar to that of 4 parts.
[0072] Example 4 The ultraviolet absorption performance test of the environmentally friendly stabilizer prepared by the present invention is as follows:
[0073] Using tetrahydrofuran as solvent, the main stabilizer was prepared into 3.5×10 -5 mol / L solution, test the UV absorption performance of the sample, the UV absorption spectrum is as follows Figure 6 shown.
[0074] from Figure 6 It can be seen that the main stabilizer has strong absorption at 270-370nm and has good ultraviolet absorption performance.
[0075] The stability of the ultraviolet absorption performance of the environmentally friendly stabilizer prepared by the present invention was tested. -5After irradiating the solution with UV light for 1 day, 3 days, 1 week, and 2 weeks, the UV absorption performance of the solution was tested. The results are as follows: Figure 7 shown.
[0076] Depend on Figure 7 It can be seen that the ultraviolet absorption of the main stabilizer changes little over time, can function for a long time, and exhibits strong light stability.
[0077] The environmentally friendly stabilizer prepared by the invention can not only replace unstable chlorine atoms in PVC to degrade and inactivate the PVC, but also absorb HCl generated by the degradation of PVC, has good thermal stability, and can absorb ultraviolet rays, and is a multifunctional thermal stabilizer that resists light aging.
[0078] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an environmentally friendly stabilizer for low-calcium PVC products, characterized in that: The main stabilizer, pentaerythritol, uracil, monoglycerol stearate and PE wax are mixed in a mass ratio of 10:3:2:1:1; The preparation method of the main stabilizer comprises the following steps: S1, using anhydrous aluminum chloride as a catalyst, 3-hydroxybenzoic acid and cyanuric chloride as raw materials to carry out Friedel-Crafts reaction, after the reaction is completed, cooling, crystallizing and filtering to obtain a solid, and recrystallizing the solid to obtain intermediate I; S2, using anhydrous aluminum chloride as a catalyst, intermediate I and resorcinol as raw materials to carry out Friedel-Crafts reaction, after the reaction is completed, pouring the reaction product into a mixed solution containing ice, water and hydrochloric acid to hydrolyze the catalyst, and then standing, heating distillation, vacuum filtering, and drying to obtain intermediate II; S3, reacting intermediate II with calcium perchlorate at 60°C for 1 hour, then stopping heating and continuing the reaction for 24 hours, filtering, washing and drying to obtain intermediate III; S4. Using N,N-dimethylformamide as solvent, the intermediate III reacts with NaOH to obtain the main stabilizer.
2. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S1, the molar ratio of the 3-hydroxybenzoic acid to cyanuric chloride is 1:1.1, the molar ratio of the catalyst anhydrous aluminum chloride to the 3-hydroxybenzoic acid is 1:1, the reaction temperature is 30°C, and the reaction time is 10 hours.
3. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S2, the molar ratio of the intermediate I to the resorcinol is 1:2, the reaction temperature is 100° C., and the reaction time is 5 h.
4. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S3, the molar ratio of the intermediate II to the calcium perchlorate is 1:
2.
5. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S4, the molar ratio of the intermediate III to the NaOH is 1:2.15, the reaction temperature is 50-60° C., and the reaction time is 1 h.
6. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S1, the solid is recrystallized using an N,N-dimethylformamide aqueous solution.
7. The method for preparing an environmentally friendly stabilizer for low-calcium PVC products according to claim 1, characterized in that: In step S3, after the reaction is completed, the solid obtained by filtration is washed twice with methanol and chloroform respectively, and the washed product is dried in a 65° C. forced air oven for 3 h, and then placed in a 65° C. vacuum oven for 6 h to obtain intermediate III.
8. The environmentally friendly stabilizer prepared by the preparation method of the environmentally friendly stabilizer for low-calcium PVC products according to claim 1.
Citation Information
Patent Citations
One-step process for preparing zinc cyanurate / calcium cyanurate compound polyvinyl chloride (PVC) stabilizer and application of compound PVC stabilizer
CN106432956A
Calcium-zinc compound stabilizer for PVC and production technology process of calcium-zinc compound stabilizer
CN110343321A